2022
DOI: 10.1021/acs.jpclett.2c00069
|View full text |Cite
|
Sign up to set email alerts
|

Collective Behavior of Urease pH Clocks in Nano- and Microvesicles Controlled by Fast Ammonia Transport

Abstract: The transmission of chemical signals via an extracellular solution plays a vital role in collective behavior in cellular biological systems and may be exploited in applications of lipid vesicles such as drug delivery. Here, we investigated chemical communication in synthetic micro- and nanovesicles containing urease in a solution of urea and acid. We combined experiments with simulations to demonstrate that the fast transport of ammonia to the external solution governs the pH–time profile and synchronizes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Given the narrow parameter domain where stable oscillations exist, reliable predictions of the reaction kinetics are indispensible for the design of experiments that demonstrate the oscillatory behavior. Furthermore, a faithful model of a single pH oscillator is a crucial prerequisite for understanding communication of vesicles and synchronization of rhythms. ,− …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the narrow parameter domain where stable oscillations exist, reliable predictions of the reaction kinetics are indispensible for the design of experiments that demonstrate the oscillatory behavior. Furthermore, a faithful model of a single pH oscillator is a crucial prerequisite for understanding communication of vesicles and synchronization of rhythms. ,− …”
Section: Discussionmentioning
confidence: 99%
“…The dynamical system in eq 10 can be interpreted as the reaction rate equations of the following effective system of involume reactions (Figure 1e): (11) amended by the exchange reactions in eq 5 of S and H + with the reservoir and the decay of P, see the first reaction in eq 6 (Figure 1d). Thus, the product P has two channels to escape from the vesicle: directly and after protonation with an effective rate.…”
Section: Model Reductionmentioning
confidence: 99%
“…Within this framework, systems chemists generally adopt a bottom-up approach to design chemical systems (or protocells) able to self-assemble in highly ordered supramolecular structures and/or to produce self-organised behaviours that accomplish complex functions without replicating the complex biological environment typical of the living cells. In this way, distinctive processes that characterise modern cells were successfully reproduced: these include, but are not limited to, collective behaviour and communication [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], energy harvesting [ 24 , 25 , 26 ] and metabolism [ 27 , 28 ]. Another common natural mechanism that has been extensively studied and mimicked by using synthetic systems is self-reproduction or division, which is the subject of the next sections of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…To date, various artificial bioreactors have been developed and utilized to understand a wide range of catalytic transformations under confinement. These include liposomes, , microemulsions, , polymersomes, , polymeric capsules, , metal–organic frameworks (MOFs), , covalent organic frameworks (COFs), , hydrogels, , and deoxyribonucleic acid (DNA) nanostructures. , These robust architectures not only stabilize the native conformations of enzymes and protect them from harmful external conditions such as acidic pH, temperature, protease digestion, and denaturation, but also enhance the enzymatic activity via stabilization of the active site, modulation of chemical activity, and enhanced mass transport. For example, Liang et al demonstrated enhanced activity of encapsulated catalase and urease inside the porous cavity of hydrophilic MOF, while negligible or no activity was observed inside hydrophobic MOF .…”
Section: Introductionmentioning
confidence: 99%